Exploring the Mechanism Underlying the Protective Effect of Mulberry Leaf Flavonoid Extract on a Cellular Model of Diabetic Encephalopathy Using Network Pharmacology - XU Han, LI Liang, CHAI Tao, DU Hongyan, LI Xueli, JIANG Yan (Shipin Kexue)
Objective: To explore the protective mechanism of mulberry leaf flavonoid extract (MFE) on a cellular model of diabetic encephalopathy (DE) by the combined use of network pharmacology and molecular biology. Methods: DE model was induced by subjecting PC12 cells to chronic high-glucose stimulation. Cell viability, oxidative damage indexes, apoptosis rate, and advanced glycation end products (AGEs) content were determined after 48 h intervention with MFE. Key targets and pathways for MFE intervention in DE were selected by network pharmacology, and molecular docking of the major components of MFE to the key targets was performed. Western blot (WB) was used to verify the results from network pharmacology. Results: Intervention with MFE effectively reduced the accumulation of AGEs and reactive oxygen species and inhibited cell apoptosis while alleviating oxidative stress damage and iron overload in DE cells, which showed significantly protective effects on the DE cell model. Network pharmacology revealed that the key signaling pathways for MFE intervention in DE might be AGEs-receptor for advanced glycation end products (AGEs-RAGE) signaling pathway in diabetic complications, mitogen-activated protein kinase (MAPK), and tumor necrosis factor (TNF) signaling pathways, and MAPK14, protein kinase B1 (AKT1), TNF, MAPK1, and MAPK8 might be potential targets. Furthermore, molecular docking confirmed stable binding affinities between the major components of MFE and these potential targets. WB results indicated that MFE may improve antioxidant capacity and inhibit ferroptosis by activating the downstream expression of phosphatidylinositol 3-kinase (PI3K)/AKT/nuclear factor erythroid-2-related factor 2 (Nrf2)/glutathione peroxidase (GPX) in the AGEs-RAGE signaling pathway. Meanwhile, MFE may inhibit the downstream expression of MAPK14/nuclear factor κB (NF-κB)/caspase-3 in the AGEs-RAGE signaling pathway, reduce the expression of pro-inflammatory factors such as TNF-α, and effectively reverse inflammatory injury and apoptosis, thus protecting the DE cell model from high glucose-induced injury. The WB results corresponded to the key targets and pathways selected by network pharmacology. Conclusion: MFE ameliorates high glucose-induced injury in PC12 cells through multiple pathways and targets.